Organic geochemistry of the Paleoproterozoic here's your chance Pb/Zn/Ag deposit - Holman, Alexander Ian (Curtin University, 2014)
This PhD has explored the application of novel organic geochemical techniques to the Paleoproterozoic Here’s Your Chance Pb/Zn/Ag deposit. Analysis of organic matter preserved within the kerogen / mineral matrix, combined with stable carbon and sulfur isotope measurements, revealed evidence of the microbial environment present during deposition. Pyrolysis experiments showed that sulfide minerals may influence the processes of organic maturation. This research has demonstrated the great potential utility of organic geochemistry in ore deposit exploration.